COVID-19 cardiac injury: Implications for long-term surveillance and outcomes in survivors - Mitrani, Raul D. (Heart Rhythm, 2020)
Up to 20%–30% of patients hospitalized with coronavirus disease 2019 (COVID-19) have evidence of myocardial involvement. Acute cardiac injury in patients hospitalized with COVID-19 is associated with higher morbidity and mortality. There are no data on how acute treatment of COVID-19 may affect the convalescent phase or long-term cardiac recovery and function. Myocarditis from other viral pathogens can evolve into overt or subclinical myocardial dysfunction, and sudden death has been described in the convalescent phase of viral myocarditis. This raises concerns for patients recovering from COVID-19. Some patients will have subclinical and possibly overt cardiovascular abnormalities. Patients with ostensibly recovered cardiac function may still be at risk of cardiomyopathy and cardiac arrhythmias. Screening for residual cardiac involvement in the convalescent phase for patients recovered from COVID-19–associated cardiac injury is needed. The type of testing and therapies for post COVID-19 myocardial dysfunction will need to be determined. Therefore, now is the time to plan for appropriate registries and clinical trials to properly assess these issues and prepare for long-term sequelae of “post–COVID-19 cardiac syndrome.”